THE PERSPECTIVE OF THE QURAN AGAINST ENVIRONMENTAL EDUCATION - Muhammad Puadi Harahap, Achyar Zein, Edi Saputra (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2019)
Abstract: A major problem in this research is how the perspective of the Koran Against environmentaleducation. This research aims to find out: 1. Check environmental education contained in theQur’an, 2. Knowing the urgency of education the environment that exists in the Koran witheducation today. This research approach tahlili, on the basis of the view that in any series ofQur’an teachings, there are clues and warnings that contains the values of education, eitherexplicitly or implicitly. Studies in the Quran known as tafsir method that each has its own characteristics,namely: Tahlili Muqaran, Ijmali, and Maudu’i. The selected method in this research is the ManhajTahlili (analytical methods). The results showed bahwaperspektif the Koran against environmentaleducation includes the creation, preservation, and management of environmental pengerusakan,therefore, environmental education include the survival of human beings , then this very urgenteducation is done at present, particularly the education lingkungn life based on religion, becauseone of the solution of the environmental damage is now the religious-based education environment.Keyword: Viewpoint, Living Environment and Edication